Avaliação multicritério de desempenho da governança da gestão de processos no Tribunal de Justiça de Santa Catarina: uma proposta construtivista - Reis, Cassiano (2017)
The Judiciary, like all Public Administration, seeks to become more efficient, productive, and expedite the jurisdictional provision. There is a special need to improve the judicial administration. The Santa Catarina Court of Justice (TJSC) is also involved in trying to improve its management by adopting new mechanisms, tools and administrative practices. Due to the need to monitor execution and seek continuous improvement in its business processes, the TJSC has an Business Processes Office (BPO), which is responsible for process management governance. However, it faces challenges to be institutionalized, which directly implicate in its managerial process and resource prioritization. This context induces that practices and instruments that allow support and encouragement to the management of the EPN and, consequently, to the governance of process management, are well received by its managers. Thus, this study aims to construct a multicriteria performance evaluation model to support governance of case management in the Santa Catarina Court of Justice, based on a constructivist view. The approach is mixed qualitative and quantitative, and the research strategy makes use of case study and bibliographic research, and the collection appropriates primary and secondary data. In order to expand the researcher's understanding of the subject, the ProKnow-C instrument was used to support the selection of a bibliographical portfolio with scientific recognition and aligned to the theme as perceived by the researcher. This process also supported the critical analysis of the selected literature, seeking to identify knowledge gaps and opportunities for scientific contribution. In order to carry out the case study, the methodology called MCDA-C (Multicriteria Methodology of Decision Support - Constructivist) was used, which enabled the identification and organization of the objectives and concerns of the manager/decision maker, and the structuring of these in a set of criteria to allow the integrated measurement of governance of process management in the TJSC. The multicriteria model was constructed with 8 strategic areas of concern (Key Points of View) and 50 evaluation indicators (criteria). The verification of the current status quo of the model also allowed to identify the strengths and criteria that need improvement. Among these, improvement actions were proposed for performance enhancement, allowing to show the consequences of these actions in the criteria (local level) and in the model (global level).